2003
DOI: 10.1017/s0020818303574069
|View full text |Cite
|
Sign up to set email alerts
|

Multilateral Determinants of Regionalism: The Effects of GATT/WTO on the Formation of Preferential Trading Arrangements

Abstract: Preferential trading arrangements (PTAs) have spread widely over the past fifty years. During the same era, multilateral openness has grown to unprecedented heights, spurred by the General Agreement on Tariffs and Trade (GATT) and its successor, the World Trade Organization (WTO). If the cornerstone of the manifestly successful multilateral regime is nondiscrimination, why have its members increasingly resorted to preferential liberalization? We argue that developments at the heart of GATT/WTO encourage its me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
109
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(113 citation statements)
references
References 48 publications
2
109
0
2
Order By: Relevance
“…Some studies have focused in aspects beyond the economic determinants. Mansfield and Reinhardt (2003) offer a more political explanation, arguing that one of the main determinants of regional trade agreements are developments at the multilateral level, with difficulties in GATT/WTO negotiations prompt countries to engage in regionalism. Mansfield, Milner, and Rosendorff (2002) empirically find that pairs of democratic countries are more likely to form a FTA, a result confirmed by Wu (2004) that also claims that economic and trade uncertainty matter.…”
Section: Literature: Empirical Analysis Of Fta Formationmentioning
confidence: 99%
“…Some studies have focused in aspects beyond the economic determinants. Mansfield and Reinhardt (2003) offer a more political explanation, arguing that one of the main determinants of regional trade agreements are developments at the multilateral level, with difficulties in GATT/WTO negotiations prompt countries to engage in regionalism. Mansfield, Milner, and Rosendorff (2002) empirically find that pairs of democratic countries are more likely to form a FTA, a result confirmed by Wu (2004) that also claims that economic and trade uncertainty matter.…”
Section: Literature: Empirical Analysis Of Fta Formationmentioning
confidence: 99%
“…Büthe and Milner (2008) show that PTAs can also increase foreign direct investment because international rules allow governments in developing countries to credibly commit to liberalization. Mansfield and Reinhardt (2003) argue that PTAs are useful as bargaining tactics in multilateral trade negotiations.…”
Section: Theorymentioning
confidence: 99%
“…Few researchers have attempted to estimate the overall effect of the GSP+ One recent study by Ozden and Reinhardt finds that the U+S+ GSP is not associated with an increase in trade+ 27 We expand their analysis by surveying all preference schemes in a variety of political contexts+ This allows us to quantify the effect of GSP-type preferences around the world, and to study the interaction between the GATT0WTO and the GSP+ To summarize, the concepts of standing and embeddedness can help one understand when and for whom international institutions matter+ In the domain of trade, the GATT0WTO should promote exchange not merely among formal members, 26+ Viner 1950 introduced criteria for evaluating PTAs: agreements can be said to increase welfare if they lead to more trade creation than trade diversion+ His criterion was subsequently used in empirical studies; see, for example, Corden 1976;Bhagwati and Panagariya 1996;Frankel 1997;and Lawrence 1999, most of which found that PTAs increase trade when they lead to significant reductions in trade barriers and when the signatories trade extensively with each other+ For recent work on the political origins of PTAs, see Mansfield and Reinhardt 2003;andMilner 1999+ 27+ Ozden andReinhardt 2005+ but more broadly among all countries and territories with legal standing+ Moreover, the GATT0WTO should be evaluated along with other trade agreements+ The remainder of the article addresses these propositions+…”
Section: Unidirectional Trade Agreements: the Generalized System Of Pmentioning
confidence: 99%